STUDYING THE GEOLOGICAL STRUCTURE OF THE SOUTH-WESTERN SPURS OF THE GISSAR REGION WITH THE PURPOSE OF IDENTIFYING OIL AND GAS CONTAINMENT - Avlakulov Abdimajit Meyliyevich (American Journals Publishing, 2024)
The article presents data from a study of gravimetric and other studies in order to determine the presence of hydrocarbon reserves in the southwestern spurs of the Gissar region, which are substantiated by the results of prospecting and exploration drilling in this area.
Keywords: Southeastern part of the Gissar region, gravity exploration, geological survey, thrust, gas and oil areas, oil and gas potential.